2010
DOI: 10.1097/iae.0b013e3181bd2d23
|View full text |Cite
|
Sign up to set email alerts
|

Microperimetric Retinal Changes in Myopic Choroidal Neovascularization Treated With Intravitreal Ranibizumab

Abstract: Intravitreal ranibizumab injections seemed to positively influence retinal functional status in patients with myopic choroidal neovascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Although the short-term results have demonstrated significant visual improvement following anti-VEGF therapy, the longer term visual outcomes appeared more variable. 14,[26][27][28] In addition, many previous studies have included both treatment naïve cases and previously treated eyes, as well as subfoveal and non-subfoveal CNV in the series, making comparison of results more difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Although the short-term results have demonstrated significant visual improvement following anti-VEGF therapy, the longer term visual outcomes appeared more variable. 14,[26][27][28] In addition, many previous studies have included both treatment naïve cases and previously treated eyes, as well as subfoveal and non-subfoveal CNV in the series, making comparison of results more difficult.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 In the past few years, various studies have demonstrated the short-term efficacy of intravitreal antivascular endothelial growth factor (VEGF) agents in treating myopic CNV, including both bevacizumab [8][9][10][11][12][13][14][15][16][17][18] and ranibizumab. [18][19][20][21][22][23][24][25] Most of the studies have demonstrated significant mean visual improvement after anti-VEGF therapy and the beneficial effects were maintained at 12 months. In addition, several more recent studies have also reported the longer term visual outcomes of up to 2 years following intravitreal bevacizumab treatment for myopic CNV.…”
Section: Introductionmentioning
confidence: 99%
“…Varano et al [188] performed microperimetry studies and showed an improvement in retinal sensitivity at 36 weeks after ranibizumab.…”
Section: Treatment Of Myopic Cnvmentioning
confidence: 99%
“…A single dose injection like with ranibizumab, may constitute a better option in an off-label therapy and avoid unnecessary risks and expenses from extra intravitreal injections [188,197]. …”
Section: Treatment Of Myopic Cnvmentioning
confidence: 99%
“…On the other hand, OCT has played a useful role in guiding retreatment in most studies evaluating the efficacy of anti-VEGF therapy in myopic CNV, whereas no study has specifically addressed the option of using OCT instead of FA [7,8,9,10,11,12,13,14,15,16,17]. …”
Section: Introductionmentioning
confidence: 99%